Modeling and measurement of torqued procession in radio pulsars - Tiplady, Adrian John (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2005)
The long term isolated pulsar monitoring program, which commenced in 1984 using the 26 m radio telescope at the Hartebeeshoek Radio Astronomy Observatory (HartRAO), has produced high resolution timing residual data over long timespans. This has enabled the analysis of observed spin down behaviour for 27 braking pulsars, most of which have dataspans longer than 14 years. The phenomenology of observed timing residuals of certain pulsars can be explained by pseudo periodic effects such as precession. Analytic and numerical models are developed to study the kinematic and dynamic behaviour of isolated but torqued precessing pulsars. The predicted timing residual behaviour of the models is characterised, and confronted with timing data from selected pulsars. Cyclic variations in the observed timing residuals of PSR B1642-03, PSR B1323-58 and PSR B1557-50 are fitted with a torqued precession model. The phenomenology of the observed timing behaviour of these pulsars can be explained by the precession models, but precise model fitting was not possible. This is not surprising given that the complexity of the pulsar systems is not completely described by the model. The extension of the pulsar monitoring program at HartRAO is used as motivation for the design and development of a new low cost, multi-purpose digital pulsar receiver. The instrument is implemented using a hybrid filterbank architecture, consisting of an analogue frontend and digital backend, to perform incoherent dedispersion. The design of a polyphase filtering system, which will consolidate multiple processing units into a single filtering solution, is discussed for future implementation.
Keywords: Pulsars; Radio telescopes; Radio astronomy; Precession; Hartebeeshoek Radio Astronomy Observatory (HartRAO)